Physical and chemical caharacteristics of neurological injury in an avian model of primary generalized epilepsy - Kendall, Edward (Image analysis and stereology, 2002)
This study was undertaken to determine if the epileptic chicken phenotype exhibited unique physical and chemical neurological changes. MethodsQuantitative 1H-MRI/MRS measurements were performed on adult control (Rr) and epileptic (rr) chickens. The metrics included nuclear relaxation rate, diffusion rate and concentration of metabolites associated with neuronalcells. Comparisons were performed using Students t or Mann-Whitney tests according to the data distribution. Results Proton density measurements detected no significant difference in density among the cerebral hemispheres and optic lobes within the control and epi birds, nor between bird phenotypes.Thus, within experimental error it appears that brain tissue density is similar in adult control and epi birds. Volume calculation from images spanning the entire brain confirmed that a consistent feature of the epi genotype was megalencephaly. Nuclear relaxation (T2 ) values obtained for the control bird were within the normal variant range for neuronal tissue. However, T2's of the epi birds were significantly higher than that of the controls ((158 ms versus 123 ms). Similarly, in the diffusion data there was no apparent hemispheric bias. The optic lobes of the control animals exhibitedan apparent diffusion coefficient significantly lower than that foundfor the cerebrum (Table 2). Interestingly, this differential was not apparent in the epi birds. The control birds across all regions of interest exhibited an ADC significantly less than that of the epi birds. Quantitative 'Hspectroscopy using tissue extracts collected immediately after sacrifice revealed phenotypic differences in lactate, glutamate, creatine and NAA but not GABA. A reduction in NAA was detected in the cerebrum of epi birds. (Abstract truncated at 2000 characters).
Keywords: Epilepsija generalizirana; Epilepsy, generalized; Magnetic resonance imaging; Magnetna resonanca; Možgani, kemija; Nuclear magnetic resonance; Bolezen, živalski modeli; Brain chemistry; Difuzija; Disease models, animal; Chickens; Fenotip; Mali možgani; Phenotype; Optični lobus; Water; Piščanci; Diffusion; Cerebellum; Voda; Chemistry; epilepsija; možgani; Optic lobe; spektroskopija